Induction of Intestinal Th17 Cells by Flagellins From Segmented Filamentous Bacteria - Wang, Yanling; Yin, Yeshi; Chen, Xin; Zhao, Yongjia; Wu, Yichen; Li, Yifei; Wang, Xin; Chen, Huahai; Xiang, Charlie (Frontiers in Immunology, 2019)
T-helper-17 (TH17) cells are a subset of CD4+ T cells that are characterized by the production of the cytokine interleukin (IL)-17 and play key roles in protecting the host from bacterial and fungal infections, particularly at the mucosal surface. These are abundant in the small intestinal lamina propria (SILP) and their differentiation are associated with the colonization of the intestinal flora. Segmented filamentous bacteria (SFB) drew the attention of researchers due to their unique ability to promote a Th17-fostering environment. Recent work has highlighted that SFB use microbial adhesion-triggered endocytosis (MATE) to transfer SFB antigenic proteins into small intestinal epithelial cells (SI ECs) and modulate host immune homeostasis. However, which components of SFB are involved in this immune response process remains unclear. Here, we examined the roles of SFB flagellins in Th17 cells induction using various techniques, including ELISA, ELISPOT, and RNA-seq in vitro and in vivo. The results showed that the immune function of SFB flagellins is similar to SFB, i.e., induces the appearance of CD4+ T helper cells that produce IL-17A, IL-17F, and IL-22 (Th17 cells) in the lamina propria. In addition, treatment of mice with SFB flagellins resulted in a significant increase in the expression of genes associated with the IL-17 signaling pathway, such as IL-6, IL-1β, TNF-α, IL-17A, IL-17F, and IL-22. In addition, SFB flagellins have an intimate relationship with intestinal epithelial cells, influencing the expression of epithelial cell-specific genes such as Nos2, Duox2, Duoxa2, SAA3, Tat, and Lcn2. Thus, we propose that SFB flagellins play a significant role in the involvement of SFB in the induction of intestinal Th17 cells.